The Fear of Freedom : Politicians and the Independence and Accountability of Financial Sector Supervisors - Taylor, Michael; Quintyn, Marc.; Ramirez, Silvia (Washington, D.C. : International Monetary Fund, 2007)
Compared with the case of central bank independence, independence for financial sector supervisors remains more controversial. This paper analyzes changes in independence and accountability arrangements in a set of 32 countries that overhauled their legal and/or institutional frameworks for supervision in recent years. Despite improvements, there is strong evidence that the endorsement of independence remains half-hearted, which shows itself through either overcompensation on the accountability side, or resort to political control mechanisms. The latter could potentially undermine the agency's credibility. The results indicate that policymakers still need to be persuaded of the long-term benefits of independence for financial sector soundness, and of the potential for a virtuous interaction between independence and accountability, if the arrangements are well-designed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet